IMPLIKASI ACFTA TERHADAP TENAGA KERJA TEKSTIL DAN PRODUK TEKSTIL INDONESIA - NINA NIKEN LESTARI, SH A.21211056, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
ABSTRACTGlobalization of the international community in the 21st century is characterized by a climate of intensified globalization. In 2010, the Southeast Asian countries that are members of the ASEAN ( Association of South East Asian Nation ) have agreed Asean China Free Trade Agreement or CAFTA with the Chinese state . Started in 2004, the ASEAN countries have signed the CAFTA , the free trade agreement to start in China with various provisions on trade between ASEAN and China - such as import duty was gradually reduced . On schedule then in 2010, the CAFTA entered the category of normal track 1 on January 1, 2010. Amongst ASEAN countries will be held on ASEAN Connectivity ( lane nexus Southeast Asia ), which is anticipated by the Indonesian government with the operation of the Port Socah 2020. On the other hand the various parties concerned CAFTA agreement will weaken the national economy , further threatening layoffs will occur and lead to rising unemployment in Indonesia due to the competitiveness of Indonesian products are low , and the people unprepared to face the global competition . Competitiveness is synonymous with the uniqueness of a product compared with other regions made . In 2010 Southeast Asian countries that are members of the ASEAN ( Association of South East Asian Nation ) have agreed Asean China Free Trade Area or ACFTA with China. Various parties concerned the deal would weaken the national economy, further threatening trade for domestic industrial products and led to the rampant layoffs . ABSTRAKGlobalisasi dunia internasional pada abad ke-21 ini ditengarai dengan iklim globalisasi yang semakin menguat. Pada tahun 2010 ini negara Asia Tenggara yang tergabung dalam ASEAN (Association of South East Asian Nation) telah menyepakati China Asean Free Trade Agreement atau CAFTA dengan negara China. Dimulai pada tahun 2004 negara-negara ASEAN telah menandatangani CAFTA tersebut, yakni kesepakatan untuk memulai perdagangan bebas dengan Cina dengan berbagai ketentuan tentang perdagangan antara ASEAN dan Cina seperti bea masuk yang secara bertahap dikurangi. Sesuai jadual maka pada tahun 2010 ini CAFTA memasuki katagori normal track 1 pada tanggal 1 Januari 2010. Diantara sesama Negara ASEAN akan diselengarakan ASEAN Connectivity (jalur perhubungan Asia Tenggara), yang diantisipasi oleh pemerintah Indonesia dengan pengoperasian Pelabuhan Socah tahun 2020 nanti. Di sisi lain berbagai pihak mengkhawatirkan kesepakatan CAFTA ini akan melemahkan perekonomian nasional, selanjutnya mengancam akan terjadi banyaknya PHK dan berujung pada meningkatnya jumlah pengangguran di Indonesia disebabkan daya saing produk Indonesia yang rendah, dan ketidaksiapan rakyat menghadapi persaingan global. Pada tahun 2010 negara Asia Tenggara yang tergabung dalam ASEAN (Association of South East Asian Nation) telah menyepakati Asean China Free Trade Area atau ACFTA dengan negara China. Berbagai pihak mengkhawatirkan kesepakatan ini akan melemahkan perekonomian nasional, selanjutnya mengancam perdagangan untuk produk-produk industri domestic dan berujung pada maraknya PHK.